PENERAPAN KAJIAN LINGKUNGAN EKSTERNAL DAN INTERNAL DALAM RANGKA FORMULASI STRATEGI BISNIS INDUSTRI KECIL KERAJINAN ROTAN - Dano Saputra; S. Pantja Djati; Meitiana . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2007)
The purpose of this research is to analyze the intern and extern environment that create strategic factors; they are opportunity, threat, strength and weakness. The result from this research will reveal whether the rattan industry has been conducted the strategy to leverage the opportunity and to avoid the threat; to maximize strength and minimize weakness. This research has been done toward the small rattan Industry in Palangkaraya by using 35 total respondents that are including the rattan expert workers who also act as the business owners. EFAS, IF AS and SWOT Matrix are used to analyze extern and intern environment. The result revealed that small rattan industry has not been conducted the extern and intern analysis in developing their business strategy. The recommended business strategy is WO Strategy, which means the business should manage the intern weakness.